From waste to resource: King coconut biochar as a green adsorbent for bisphenol A removal - Hashinika Matharage; Mahesh Jayaweera; Nilanthi Bandara; Jagath Manatunge; Daham Jayawardana; Janith Dissanayake (Case Studies in Chemical and Environmental Engineering)
The widespread presence of BPA in water bodies poses significant environmental and health concerns, highlighting the need for sustainable and efficient removal technologies. This study presents an innovative approach for BPA remediation using biochar derived from king coconut shells—a readily available agricultural waste and by-product of a popular drink in many parts of Asia. Biochar pyrolyzed at 800 °C exhibited the highest removal efficiency, which was significantly enhanced to 80.1 ± 0.9 % following HCl activation. Further reduction of the particle size from 1.0–4.0 mm to 75–105 μm resulted in complete (100 %) removal of BPA. Batch adsorption experiments revealed optimal removal at pH 3–7, with a dosage of 5.0 g/L and an initial BPA concentration of 100.0 ppm. The adsorption process was best described by the Langmuir isotherm model (R2 = 0.99), with a maximum capacity of 39.53 mg/g. Kinetic studies demonstrated that the pseudo-second-order model accurately represented the adsorption dynamics, implying chemisorption as the rate-limiting step. Regeneration experiments using ethanol demonstrated the reusability of the adsorbent, maintaining over 79.6 % removal efficiency after five consecutive cycles. These findings highlight the effectiveness of KBC800–HCl as a sustainable and high-performance adsorbent, demonstrating the broader potential of agricultural waste valorization in environmental remediation.